2015
DOI: 10.1007/s00167-015-3638-0
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic anterior talofibular ligament repair for lateral instability of the ankle

Abstract: Although several arthroscopic procedures for lateral ligament instability of the ankle have been reported recently, it is difficult to augment the reconstruction by arthroscopically tightening the inferior extensor retinaculum. There is also concern that when using the inferior extensor retinaculum, this is not strictly an anatomical repair since its calcaneal attachment is different to that of the calcaneofibular ligament. If a ligament repair is completed firmly, it is unnecessary to add argumentation with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 18 publications
2
102
0
Order By: Relevance
“…24 An 18-gauge hollow needle with No. 2-0 nylon thread penetrates the ATFL inferior limb remnant 25,26 through the AAL or ST portal depending on the accessibility to the remnant. A suture passer, such as the Micro SutureLasso (Arthrex, Naples, FL) or SpeedSnare (Zimmer Biomet), is also useful for grasping the ATFL remnant.…”
Section: Step 4: Tunnel Creationmentioning
confidence: 99%
“…24 An 18-gauge hollow needle with No. 2-0 nylon thread penetrates the ATFL inferior limb remnant 25,26 through the AAL or ST portal depending on the accessibility to the remnant. A suture passer, such as the Micro SutureLasso (Arthrex, Naples, FL) or SpeedSnare (Zimmer Biomet), is also useful for grasping the ATFL remnant.…”
Section: Step 4: Tunnel Creationmentioning
confidence: 99%
“…The knot suture anchor repair procedure was performed according to a previous report ( Figure 1, A and C). 25 After the ATFL insertion at the distal fibula was identified (a mean 10-11 mm proximal to the distal tip of the fibula), 1 suture anchor (3.0-mm SutureTak) was placed at the fibular ATFL footprint. The ATFL remnant was penetrated by a tissue-penetrating instrument.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…‡ Generally, the suture anchors for ankle ligament repair can be divided into knot and knotless. Previously, Takao et al 25 described a simplified repair technique of the lateral ligament alone with a knot suture anchor, which avoids additionally tightening the inferior extensor retinaculum. Moreover, Li et al 16 repaired the ATFL with a knot suture anchor technique and reported that arthroscopic repair of the ATFL produced favorable magnetic resonance imaging outcomes with excellent functional outcomes 2 years postoperatively.…”
mentioning
confidence: 99%
“…They can be divided into 2 categories: ligament repair or ligament reconstruction using a tendon graft or transfer. [3][4][5][6][7][8][9][10][11][12] The surgical procedure should be selected based on the tissue quality determined during arthroscopic assessment of the ATFL remnant. 11,13 The aim of this article was to present an arthroscopic technique for all-inside ATFL repair that allows for restoration of the ankle joint stability in a minimally invasive way.…”
mentioning
confidence: 99%